Pedestrian perception on walkability in the royal town of Klang: a case study of Jalan Tengku Kelana and Jalan Dato Hamzah, Bandar Klang - Abdul Rahim, Abdul Mun’im; Asif, Nayeem; Abdullah, Fadzidah; Sanusi, Aliyah Nur Zafirah; Yusof, Zeenat Begam; Azmin, Aida Kesuma; Ismail, Mohd Noorizhar (International Organization Center of Academic Research, 2023)
The Klang Local Draft Plan 2035 has identified accessibility issues in some tourist locations and inconsistent pedestrian walkways that hinder pedestrian movement. Therefore, this paper aims to assess the spatial characteristics of pedestrian networks and the walkability in Klang to enhance visitors' walking experience. A quantitative design using a structured questionnaire based on walkability criteria and measurement framework was employed to achieve this. The research findings provide four key recommendations for improving the pedestrian environment, pathway network, pedestrian infrastructure, and maintenance. The significance of this study lies in its contribution to planners' and architects' efforts to create better pedestrian network access in urban areas. Additionally, it aligns with the 11th Sustainable Development Goal of creating sustainable cities and communities by enhancing road safety and providing access to affordable, safe, sustainable transport systems. Furthermore, this research can guide future urban research, walking and accessibility initiatives, and evaluations of proposals to revitalize historic towns and prevent unused urban spaces.